2022
DOI: 10.1021/acsami.1c24229
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Charge-Switchable and Size-Transformable Thermosensitive Nanocomposites for Chemo-Photothermal Eradication of Bacterial Biofilms in Vitro and in Vivo

Abstract: The appearance of multidrug-resistant bacteria and their biofilms presents a serious threat to modern medical systems. Herein, we fabricated a novel gold-nanorod-based chemo-photothermal-integrated antimicrobial platform with surface-charge-switchable and near-infrared (NIR)-induced size-transformable activities that show an enhanced killing efficiency against methicillin-resistant Staphylococcus aureus (MRSA) in both planktonic and biofilm phenotypes. The nanocomposites are prepared by in situ copolymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…108 Photodynamic therapy (PDT) and photothermal therapy (PTT) have also been suggested as possible methods of biofilm targeting. [115][116][117] They are considered to be minimally invasive and reliable. In these methods, reactive oxygen species (ROS) This journal is © The Royal Society of Chemistry 2022 that affect bacterial cells and the biofilm at large through oxidation are generated as a result of irradiation and release of photosensitizers and other loaded agents, respectively, by light of fixed wavelength.…”
Section: Alternative Strategies For Targeting Biofilmsmentioning
confidence: 99%
“…108 Photodynamic therapy (PDT) and photothermal therapy (PTT) have also been suggested as possible methods of biofilm targeting. [115][116][117] They are considered to be minimally invasive and reliable. In these methods, reactive oxygen species (ROS) This journal is © The Royal Society of Chemistry 2022 that affect bacterial cells and the biofilm at large through oxidation are generated as a result of irradiation and release of photosensitizers and other loaded agents, respectively, by light of fixed wavelength.…”
Section: Alternative Strategies For Targeting Biofilmsmentioning
confidence: 99%
“…The era of antibiotics is progressively coming to an end due to the emergency of multidrug-resistant bacteria. It has been reported that multidrug-resistant bacteria cause at least 700,000 deaths worldwide each year, including 23,000 deaths in the United States and 25,000 deaths in the European Union [ 3 ]. The World Health Organization predicts that 10 million people worldwide will die from bacterial infections by 2050 if no efforts are made to reduce bacterial resistance or develop new antibiotics [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial agents involve antibiotics, natural extracts, cationic polymers, antimicrobial peptides, , and antibacterial materials. Most of them are not able to pass through the biofilm barriers efficiently, thus limiting their efficacies in the therapy of biofilm-associated infection. Mature biofilms act as barriers to antimicrobial agents by restricting their diffusion and preventing them from penetrating deeply into the matrix. Thus, novel therapeutic agents and strategies capable of fully accessing inside bacteria by penetrating the biofilm barriers for tackling biofilms are urgently needed .…”
Section: Introductionmentioning
confidence: 99%